Habitat preferences of the Critically Endangered greater Bermuda land snail Poecilozonites bermudensis in the wild. Issue 1 (25th January 2022) - Copeland, Alison; Hesselberg, Thomas
Abstract: The endemic, Critically Endangered greater Bermuda land snail Poecilozonites bermudensis is known from only two relict subpopulations. Little is known of its habitat preferences in the wild. Observations of released zoo-reared P. bermudensis suggested an affinity for limestone, which we investigated on Port's Island. Previous qualitative observations on Port's Island suggested an aversion to the litter of the invasive tree Casuarina equisetifolia, which we examined. Additionally, we hypothesized that snail abundance would increase with elevation, distance from the sea, and with increased plant species diversity. During 2 May–14 June 2018, we found 558 live P. bermudensis at 70 sites across Port's Island. We found no correlation between the number of live snails at a site and either the number of plant species, elevation or distance from the shoreline, but snails were significantly less abundant at sites dominated by C. equisetifolia . Significantly more snails were found around limestone features, indicating future reintroductions and searches for any undiscovered subpopulations should focus on limestone features where C. equisetifolia is absent.